First record of Oxyligyrus nasutus (Burmeister, 1847) (Coleoptera: Melolonthidae: Dynastinae) from Brazil, damaging plants of açaí palm Euterpe oleracea Mart. (Arecaceae) - Duarte, Paulo R. M.; Mota, Adriana A.; Santos, Antônio A. R.; Sosa-Duque, Francisco J.; Grossi, Paschoal C. (Entomological Communications, 2023)
The açaí palm plays major socioeconomic importance to human populations in North Brazil. Damages caused by pest insects in the orchards are among the main factors that limit açaí production, mainly members of Coleoptera. However, rhinoceros beetles (Dynastinae) had never been observed damaging açaí palms. Here, we noticed the first occurrence of Oxyligyrus nasutus (Burmeister, 1847) (Melolonthidae: Dynastinae: Pentodontini) attacking young açaí plants in the locality of Nova Colônia, Capitão Poço municipality, Pará state, Brazil. The species was observed digging tunnels in the soil near attacked plants. The damages happened through perforation localized at the basal stem part, where the beetles feed on the heart of the palm, preventing its development. This event is a wake-up call for local farmers to avoid the intervention of the edges of floodplains that could be the natural habitat of these insects. In addition, it also represents the first record of O. nasutus from Brazil.